Etno-social knowledge: How does knowledge of basic school teachers in Indonesia? - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Maryono Maryono; Putut Nugroho; Rahmat Perdana (Journal of Education and Learning (EduLearn), 2019)
Etnososial is learning that integrates culture and local wisdom into social learning. Indonesia is very rich with a variety of cultures and local wisdom. These cultural values and local wisdom must be used by the teacher as a material and source of learning. So from that, the purpose of this study is to know the ethnosocial knowledge of elementary school teachers and the obstacles in applying it. This research uses quantitative design with survey research design. This study used 30 teachers as respondents. The instruments used were questionnaires and interviews. The results of this study are about the knowledge of ethno-social elementary school teachers in Indonesia in good condition. It is known that the ethno-social knowledge of teachers in Bajubang District is 6.7% included in the very bad category. While 30.0% are in a bad category, 43.3% are in a good category and 20.0% are in the very good category. The teacher applies ethno-social knowledge through various methods, learning strategies, using simple learning media and using the environment as a learning resource. While the obstacles faced by teachers are the ability of different students, media and learning resources that are lacking, lack of knowledge and experience of ethno-social teachers.